ANALISIS PENGARUH PRODUK, HARGA DAN TEMPAT TERHADAP KEPUTUSAN PEMBELIAN DITOKO BUKU BOOKS & BEYOND CILANDAK TOWN SQUARE - Lucy Nancy Simatupang; Meiti Suswantari (Jurnal Manajemen, 2018)
This study aimed to determine the effect of Product, Price, and Place of the buying decision. The method used in this research is quantitative method and assessment of the results of this study based on the answers of respondents using Likert Scale. The population in this study is the Consumer Books & Beyond Cilandak Town Square and sample in this study amounted to 57 respondents. The method of analysis in this study using the Test Instrument (Validity and Reliability), Analysis Normality of data, Classical Assumption Test (Normality, multicoloniarity, Heteroskedatisitas, autocorrelation), Test Correlation Coefficient Test, linear regression, t test, Test f, and the coefficient of determination R2 . From the results of the t test (Partially), has obtained results that place the variable (X3) has a significant influence on the purchase decision and book stores Books & Beyond Cilandak Town Square. As for the Product variable (X1), and Price (X2),had no effect and no significant effect on Purchasing Decisions Books & Beyond stores.